Orchestrating neuronal networks: sustained after-effects of transcranial alternating current stimulation depend upon brain states - Neuling, Toralf; Rach, Stefan; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2013)
The interest in transcranial alternating current stimulation (tACS) has significantly increased in the past decade. It has potential to modulate brain oscillations in a frequency specific manner, offering the possibility to demonstrate a causal nature of oscillation behavior relationships. TACS is a strong candidate as a tool for clinical applications, however, to fulfill this potential, certain parameters have yet to be evaluated. First, little is known about long-lasting after-effects of tACS with respect to the modulations of rhythmic brain activity. Second, the power of endogenous brain oscillations might play a crucial role in the efficacy of tACS. We hypothesize that the duration of the after-effects of tACS is dependent on the endogenous power of oscillations. To this end, we modulated the power of endogenous occipital alpha oscillations via tACS. In two experiments, participants either had their eyes open or closed to keep endogenous alpha power either low or high while they were stimulated for 20 minutes with their individual alpha frequency (IAF) and simultaneously performing a vigilance task. After-effects on IAF power were evaluated over a course of 30 minutes with a pre stimulation period serving as baseline. After-effects were strongly dependent on IAF power. Enhanced IAF power was observed for at least 30 minutes after tACS under conditions of low endogenous IAF power, whereas, IAF power could not be further enhanced by tACS under conditions of high IAF power. The current study demonstrates, for the first time, a long lasting effect after tACS on endogenous EEG power in the range of the stimulation frequency. Additionally, we present conclusive evidence that the power of the endogenous oscillations has a critical impact on tACS efficacy. Long lasting after-effects foster the role of tACS as a tool for non-invasive brain stimulation and demonstrate the potential for therapeutic application to reestablish the balance of altered brain oscillations.